Magnetic materials for magnetoelectric coupling: An unexpected journey - Lima, A. C. (2020)
Magnetic materials for magnetoelectric coupling are reported. After an introduction of magnetoelectric effect and materials, an historical on the main developments in this field are presented. Then, the main concepts related to multiferroic and magnetoelectric materials are introduced, together with the description of the main types of magnetoelectric materials and structures. Finally, the magnetic materials used the development of magnetoelectric composites are presented and discussed, highlighting their main physico-chemical characteristics and processing methods. In this way, a complete account on concepts, materials and methods is presented in this strongly evolving research field, with strong application potential in the areas of sensors and actuators, among others.